Publication Trends from STEAM in Education from Scopus Database: Bibliometric Analysis - Edi Supriyadi; Turmudi; Jarnawi Afgani Dahlan; Dadang Juandi (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this study is to shed light on the domain of STEAM education research by employing a three-pronged strategy. This article provides a bibliometric analysis of STEAM education literature by focusing on three major research questions (RQs): RQ1. How has research on STEAM education progressed? RQ2. Who is the most influential in STEAM education research? RQ3. Which affiliations and countries are contributing to STEAM in education? This study combines quantitative analysis with descriptive methods. The evolution of STEAM education and the pattern of publishing found in Scopus, which is determined by research connections, research themes, and scientific journals, are of interest to researchers. Throughout this research, the Bibliometrix R-tool and the BiblioShiny software packages were utilized, one at a time, for data analysis, reduction, visualization, and mapping, respectively. In response to RQ1, this study found the Annual Growth Rate to be 24.19%. This finding is based on the trend of publications in STEAM in Education. The results indicate that there has been an increase in the number of journal articles devoted to this subject, which are frequently disseminated. The second question this research aims to answer is which areas of STEAM education research have the most influence. While Piperopoulos P has the top spot for the most globally mentioned documents, Perignat E holds the top spot for the most locally cited papers. In the meantime, Herro D is a writer who has contributed to the study done in the field of STEAM education. As for RQ3, it can be noted that Jeju National University and the Korea National University of Education are the top two campuses in the world regarding STEAM in Education research publications, both of which are located in South Korea.